2019
DOI: 10.1085/jgp.201912374
|View full text |Cite
|
Sign up to set email alerts
|

Progressive recruitment of distal MEC-4 channels determines touch response strength in C. elegans

Abstract: Touch deforms, or strains, the skin beyond the immediate point of contact. The spatiotemporal nature of the touch-induced strain fields depend on the mechanical properties of the skin and the tissues below. Somatosensory neurons that sense touch branch out within the skin and rely on a set of mechano-electrical transduction channels distributed within their dendrites to detect mechanical stimuli. Here, we sought to understand how tissue mechanics shape touch-induced mechanical strain across the skin over time … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…Using this approach, our prior work Petzold et al [2013] showed that the magnitude of indentation is a better predictor of the probability of behavioral response than force in C. elegans. This finding is supported by subsequent studies that directly measured mechanosensory currents in TRNs using electrophysiology [Eastwood et al, 2015, Katta et al, 2019b and has been incorporated into theoretical models of C. elegans touch sensation [Eastwood et al, 2015, Sanzeni et al, 2019. These models posit that touch-induced mechanical strain in the TRNs leads to the activation of mechano-electrical transduction channels.…”
Section: Introductionmentioning
confidence: 65%
See 4 more Smart Citations
“…Using this approach, our prior work Petzold et al [2013] showed that the magnitude of indentation is a better predictor of the probability of behavioral response than force in C. elegans. This finding is supported by subsequent studies that directly measured mechanosensory currents in TRNs using electrophysiology [Eastwood et al, 2015, Katta et al, 2019b and has been incorporated into theoretical models of C. elegans touch sensation [Eastwood et al, 2015, Sanzeni et al, 2019. These models posit that touch-induced mechanical strain in the TRNs leads to the activation of mechano-electrical transduction channels.…”
Section: Introductionmentioning
confidence: 65%
“…Other experiments have shown that wild-type C. elegans TRNs are activated mostly by high-velocity stimuli [Suzuki et al, 2003, Eastwood et al, 2015, Nekimken et al, 2017, Katta et al, 2019b. Because of the time required to acquire a z-stack, we can only measure TRN strain at steady-state and are unable to evaluate how mechanical strain is affected by varitions in stimulus speed.…”
Section: Strain-rate Dependencementioning
confidence: 99%
See 3 more Smart Citations